Preliminary study on the monitoring of glutathione S-tranferase activity toward styrene oxide by electromigration methods - Sisková, Zdenka; Glatz, Zdenĕk; Kahle, Vladislav (Journal of separation science, 2005)
A new method has been developed for the monitoring of glutathione S-tranferase (GST) detoxification activity toward styrene oxide (SO). The enzymatic reaction was carried out directly in a thermostatted autosampler vial and the formation of conjugates between glutathione (GSH) and SO was monitored by sequential MEKC runs. The determinations were performed in a 50-microm fused silica capillary using 50 mM SDS in 20 mM phosphate 20 mM tetraborate buffer (pH 8.3) as a background electrolyte; separation voltage 28 kV (positive polarity), temperature of capillary 25 degrees C, and detection at 200 nm. The method is rapid, amenable to automation, and requires only small amounts of samples, which is especially important in the case of GST isoenzyme analyses.
Keywords: Liver; Animals; Electrophoresis, Capillary; játra; elektroforéza kapilární; Substrate Specificity; In Vitro Techniques; vysokoúčinná kapalinová chromatografie; techniky in vitro; glutathiontransferasa; epoxidové sloučeniny; Glutathione Transferase; Chromatography, Micellar Electrokinetic Capillary; chromatografie micelární elektrokinetická kapilární; Chromatography, High Pressure Liquid; krysa rodu Rattus; Epoxy Compounds; zvířata; substrátová specifita; Rats